Pemberdayaan Remaja Sehat di Masa Pandemi Covid-19 Melalui Program Saung Remaja Sehat (SAREAT) - Susanti, Santi; Mulyani, Sri; Rosmiati, Tita; Maulida, Sopi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2023)
The COVID-19 pandemic has had a significant impact on various aspects of life, including the health and welfare of teenagers in various regions, including Cikunir Village, Singaparna District, Tasikmalaya Regency. This condition requires creative and innovative steps to ensure that the younger generation continues to have access to accurate health information, emotional support, and the skills needed to maintain the health of themselves and the community around them. One alternative to make this happen is through skills training in making hand sanitizer and mask connectors for entrepreneurship. This community service aims to improve the ability of teenagers in Cikunir Village in the skills of making hand sanitizers and mask connectors so that they become productive teenagers in filling their free time positively. This youth empowerment was attended by nine youth posyandu cadres. The training implementation time is one month. The results of the training showed that the teenagers were able to make hand sanitizer and mask connectors and form associations SAREAT/Healthy youth group. The youth's production is marketed to village communities and peers using two methods, namely selling directly and online. The conclusion of youth empowerment during the Covid-19 pandemic the teenagers were able to make hand sanitizer according to WHO standards and mask connectors and shapes SAREAT namely a place for youth creativity in the field of entrepreneurship. Keywords : covid-19, hand sanitizer, masks, empowerment, teenagers